2024
DOI: 10.1002/ps.8080
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and antifungal activity of novel α‐methylene‐γ‐butyrolactone derivatives containing benzothiophene moiety

Luwei Li,
Tuoping Hui,
Yuying Li
et al.

Abstract: BackgroundThe discovery of agricultural fungicide candidates from natural products is one of the key strategies to develop environment friendly agricultural fungicides with high efficiency, high selectivity, and unique mechanisms of action. Based on previous work, a series of novel α‐methylene‐γ‐butyrolactone (MBL) derivatives containing benzothiophene moiety were designed and synthesized.ResultsThe majority of the proposed compounds displayed moderate to considerable antifungal efficacy against the tested pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Thiophene-based compounds can be made quickly and have biological functions, which has provoked a lot of interest in their synthesis [4][5][6][7][8][9][10][11][12][13]. Their biological outcomes comprise antifungal, antiviral, antibacterial, anti-inflammatory, and cytotoxic characteristics [14,15]. Harit et al reported the antibacterial efficacy of thiophenebased compounds against Staphylococcus aureus, Escherichia coli, and Salmonella enterica subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Thiophene-based compounds can be made quickly and have biological functions, which has provoked a lot of interest in their synthesis [4][5][6][7][8][9][10][11][12][13]. Their biological outcomes comprise antifungal, antiviral, antibacterial, anti-inflammatory, and cytotoxic characteristics [14,15]. Harit et al reported the antibacterial efficacy of thiophenebased compounds against Staphylococcus aureus, Escherichia coli, and Salmonella enterica subsp.…”
Section: Introductionmentioning
confidence: 99%